Repeated Low-Level Blast Acutely Alters Brain Cytokines, Neurovascular Proteins, Mechanotransduction, and Neurodegenerative Markers in a Rat Model - Heyburn, Lanier; Abutarboush, Rania; Goodrich, Samantha; Urioste, Rodrigo; Batuure, Andrew; Wheel, Jaimena; Wilder, Donna M.; Arun, Peethambaran; Ahlers, Stephen T.; Long, Joseph B.; Sajja, Venkatasivasai Sujith (Frontiers in Cellular Neuroscience, 2021)
Exposure to the repeated low-level blast overpressure (BOP) periodically experienced by military personnel in operational and training environments can lead to deficits in behavior and cognition. While these low-intensity blasts do not cause overt changes acutely, repeated exposures may lead to cumulative effects in the brain that include acute inflammation, vascular disruption and other molecular changes, which may eventually contribute to neurodegenerative processes. To identify these acute changes in the brain following repeated BOP, an advanced blast simulator was used to expose rats to 8.5 or 10 psi BOP once per day for 14 days. At 24 hours after the final BOP, brain tissue was collected and analyzed for inflammatory markers, astrogliosis (GFAP), tight junction proteins (claudin-5 and occludin), and neurodegeneration-related proteins (Aβ40/42, pTau, TDP-43). After repeated exposure to 8.5 psi BOP, the change in cytokine profile was relatively modest compared to the changes observed following 10 psi BOP, which included a significant reduction in several inflammatory markers. Reduction in the tight junction protein occludin was observed in both groups when compared to controls, suggesting cerebrovascular disruption. While repeated exposure to 8.5 psi BOP led to a reduction in the Alzheimer’s disease-related proteins amyloidβ (Aβ)40 and Aβ42, these changes were not observed in the 10 psi group, which had a significant reduction in phosphorylated tau. Finally, repeated 10 psi BOP exposures led to an increase in GFAP, indicating alterations in astrocytes, and an increase in the mechanosensitive ion channel receptor protein, Piezo2, which may increase brain sensitivity to injury from pressure changes from BOP exposure. Overall, cumulative effects of repeated low-level BOP may increase the vulnerability to injury of the brain by disrupting neurovascular architecture, which may lead to downstream deleterious effects on behavior and cognition.